ESTABLISHMENT OF THE PERMISSIBLE TRAIN SPEED ON THE CURVED TURNOUTS - Patlasov, O. M.; Tokariev, S. O.; Patlasov, Ye. O. (Science and Transport Progress, 2016)
Purpose. Turnouts play a key role in the railway transportation process. One-sided and many-sided curved turnouts were railed over the last 20 years in difficult conditions (curved sections, yard necks). They have a number of geometric features, unlike the conventional one-sided turnouts. Today the normative documents prohibit laying such turnouts in curved track sections and only partially regulate the assessment procedure of their real condition. The question of establishment the permissible train speed within the curved turnouts is still open. In this regard, authors propose to set the train speed according to the driving comfort criterion using the results of field measurements of ordinates from the baseline for the particular curved turnout. Methodology. The article considers the criteria using which one can set the permissible speed on the turnouts. It defines the complexity of their application, advantages and disadvantages. Findings. The work analyzes the speed distribution along the length of the real curved turnout for the forward and lateral directions. It establishes the change rate values of unbalanced accelerations for the existing norms of the curved track sections maintenance according to the difference in the adjacent bend versine at speeds up to 160 km/h. Originality. A method for establishing the trains’ speed limit within the curved turnouts was developed. It takes into account the actual geometric position in the plan of forward and lateral turnout directions. This approach makes it possible to establish a barrier places in plan on the turnouts limiting the train speed. Practical value. The proposed method makes it possible to objectively assess and set the trains’ permissible speed on the basis of the ordinate measurement of the forward and lateral directions of the curved turnouts from the baseline using the driving comfort criteria. The method was tested using real turnouts, which are located within the Pridneprovsk Railway.